Risk of cancer associated with measures of placental glutathione S-transferase (GST-P 7-7): A comprehensive review - Ribeiro, Daniel Araki; Noguti, Juliana; César, Augusto; Pereira, Camilo Dias Seabra; Choueri, Rodrigo Brasil; Medalha, Carla Cristina; De Sá, Cristina dos Santos Cardoso; Dedivits, Rogério Aparecido; Barbisan, Luis Fernando [UNESP]; Spadari-Bratfisch, Regina Celia (My University, 2013)
Glutathione S-transferases (GSTs) are a family of crucial enzymes involved in the cell detoxification of xenobiotics. GSTs exist as homo- or hetero-dimers and have been grouped into at least seven distinct classes. The main function of GSTs is to catalyze the conjugation of reduced glutathione (GSH) to an electrophilic site of a broad range of potentially toxic and carcinogenic compounds, thereby making such compounds less dangerous and enabling their readily excretion. Placental GST, known as GST-P 7-7, is the main isoform in normal placental tissue and comprises 67% of the total GST concentration in this phase. During development, GST-P 7-7 decreases in concentration and is absent in adult tissues. Interestingly, GST-P-7-7-positive expression have been detected in adult tissues after exposure to carcinogenic agents in several experimental test-systems being, considered a reliable biomarker of exposure and susceptibility in early phases of carcinogenesis process. In this chapter, we review a series of studies involving GST-P 7-7 positive expression and cancer risk. © 2013 Nova Science Publishers, Inc. All rights reserved.